The Survival Function of the Bcr-Abl Oncogene Is Mediated by Bad-Dependent and -Independent Pathways: Roles for Phosphatidylinositol 3-Kinase and Raf - Neshat, Mehran S. (American Society for Microbiology, 2000)
The Bcr-Abl tyrosine kinase constitutively activates cytokine signal transduction pathways that stimulate growth and prevent apoptosis in hematopoietic cells. The antiapoptotic action of interleukin-3 (IL-3) has been linked to a signaling pathway which inactivates the proapoptotic protein Bad by phosphorylation through kinases such as Akt and Raf. Here we report also that expression of Bcr-Abl leads to phosphorylation of Bad in hematopoietic cells. Bad phosphorylation induced by Bcr-Abl is kinase dependent, requires phosphatidylinositol 3-kinase (PI3-kinase), and mitochondrial targeting of Raf, and occurs independently of Erk. The ability of Bcr-Abl to confer cytokine-independent survival to hematopoietic cells was compromised by inhibitors of PI3-kinase, as well as by a dominant negative form of Raf targeted to the mitochondria. Furthermore, when the capacity of Bcr-Abl to phosphorylate Bad was completely blocked by dominant negative Raf, a subpopulation of cells remained viable, providing evidence for Bad-independent survival pathways. This alternative survival pathway remained PI3-kinase dependent. Finally, Bcr-Abl, but not IL-3, inhibited the proapoptotic activity of overexpressed Bad. We conclude that the antiapoptotic function of Bcr-Abl is mediated through pathways involving PI3-kinase and Raf and that survival can occur in the absence of Bad phosphorylation.